Dental implants in oral rehabilitation after denosumab and bisphosphonate-related osteonecrosis of the jaw in a young patient: an unusual case - Salabert Noémie; Loison-Robert Ludwig; Ahossi Victorin; Hoarau David (EDP Sciences, 2024)
Patients often request oral rehabilitation after surgical resection. Here, a 19-year-old patient developed medication-related osteonecrosis of the jaw after treatment with antiresorptive therapy. After the surgical treatment for osteonecrosis, dental implants were discussed. While there is a known risk of provoking secondary osteonecrosis of the jaw in such cases, other factors should also be taken into account. This case report highlights the importance of close monitoring for patients with a history of medication that incurs a risk osteonecrosis', and the feasibility of dental implants on the surgical site in some conditions. Decisions relative to implant placement were made based on the patient's specific history, their present situation, and the potential options that were available.